The Development Strategy of ‘Cinta Mangrove Park’ Ecotourism In Mempawah Regency - Kurniati, Dewi; Dolorosa, Eva (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 14 No 3 (2020): Vol.14, No.3, 2020, 2020)
Mempawah Regency is an area located on the coast that has a wide area of mangrove forest. The mangrove forest is used to prevent abrasion and as an ecotourism area. This regency has three mangrove ecotourism; they are Mempawah Mangrove Park, Polaria Tanjung Pagar Mangrove Park and Cinta Mangrove Park. Cinta Mangrove Park is the newest mangrove ecotourism in Mempawah Regency. As the latest ecotourism, there are still some shortages, upgrading and developments that need to be done in terms of human resources, facilities and less of promotion. The aim of this research was to determine the development strategy of the Cinta Mangrove Park ecotourism. The location of the research was carried out at the Cinta Mangrove Park Ecotourism in Sungai Bakau Besar Laut Village Sungai Pinyuh Sub-District Mempawah Regency with the consideration that this location was the latest ecotourism that still has a lot of shortages and need improvement.  The selected respondents were the key informants. The analysis used was SWOT and QSPM analysis. The results of the research described that the mangrove ecotourism development strategy was a weakness-opportunity (WO) strategy. The main priority of the Cinta Mangrove Park ecotourism development strategy was to seek funding sources and attract investors to collaborate to build tourism facilities. The results of this research were expected to be a contribution in determining policies for the government and society for the development of the Cinta Mangrove Park ecotourism.